2013
DOI: 10.1016/j.jenvman.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ni phytostabilization by inoculation of Ni resistant Bacillus megaterium SR28C

Abstract: The use of metal tolerant plants for the phytostabilization of metal contaminated soil is an area of extensive research and development. In this study the effects of inoculation of Ni-resistant bacterial strains on phytostabilization potential of various plants, including Brassica juncea, Luffa cylindrica and Sorghum halepense, were studied. A Ni-resistant bacterial strain SR28C was isolated from a nickel rich serpentine soil and identified as Bacillus megaterium based on the morphological features, biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 67 publications
(90 reference statements)
3
34
0
1
Order By: Relevance
“…2011b), and copper (Cu) (Zhang et al, 2011). In some cases, increased growth and tolerance against heavy metal stress observed in PGPB inoculated plants have been explained by plant beneficial traits of PGPB and/or reduced metal uptake by plants (Rajkumar et al, 2013). However, different PGPB-hyperaccumulator associations might provide different responses, and therefore, further research is required to understand whether PGPB-inoculated plants and specific strains favor rhizoremediation of pollutants and through which mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011b), and copper (Cu) (Zhang et al, 2011). In some cases, increased growth and tolerance against heavy metal stress observed in PGPB inoculated plants have been explained by plant beneficial traits of PGPB and/or reduced metal uptake by plants (Rajkumar et al, 2013). However, different PGPB-hyperaccumulator associations might provide different responses, and therefore, further research is required to understand whether PGPB-inoculated plants and specific strains favor rhizoremediation of pollutants and through which mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent investigations addressed rhizosphere and endophytic microbial population of plants and their role on rhizoremediation in metal-polluted soils (Ma et al, 2011b;Rajkumar et al, 2013), the beneficial interactions between S. plumbizincicola and PGPB and their possible role on the rhizoremediation of multi-metal-polluted agricultural soils still remain poorly understood. The objectives of this study were to (i) isolate and characterize a beneficial bacterial strain possessing the ability to mobilize metals in soils,…”
mentioning
confidence: 99%
“…Many reports of the usefulness of bacteria strain in the plant cultivation can be found in the literature. For example, the reduction of Se(IV) [9], the suppression of S. sclerotiorum on oilseed rape [10], the phytostabilization of Ni contaminated soil [11] and the reduction of septoriatritici blotch [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, experiments with various plants revealed that the inoculation with Bacillus megatherium SR28C reduced translocation of Ni from roots to shoots compared with the control. This effect was attributed to the increased metal biosorption by Bacillus megatherium SR28C [43].…”
Section: E Influence Of Psb Isolates On Heavy Metals Uptakementioning
confidence: 99%